Association of body mass index and other factors with metabolically unhealthy status: Results from the national health examination survey IV - Suebsamran, Phalakorn; Aekplakorn, Wichai; Chamnan, Parinya; Bumrerraj, Sauwanan; Kuhiranyaratn, Piyathida; Kessomboon, Pattapong (Asia-Pacific Journal of Science and Technology, 2021)
Increasing evidence about non-proportionally high cardiovascular risk in individuals with normal body mass index (BMI) suggested a need for alternative approaches to risk classification, one of which is metabolic health status (MHS). This study aimed to estimate the prevalence of MHS, and examine the association of BMI, other factors and being metabolically unhealthy in a contemporary Thai population, using data on 19,640 participants in the National Health Examination Survey IV (NHES IV) in 2009. Metabolically unhealthy (MUH) was defined as individuals having abnormality in at least one metabolic parameter based on the International Diabetes Federation (IDF) criteria. The prevalence was estimated for the overall population and across BMI categories. Multivariable logistic regression was performed to examine the association between BMI categories, other characteristics and MUH status. The results show that the prevalence of MUH individuals in the Thai population is 73.1%. The prevalence of metabolic parameter abnormalities rose significantly with increasing BMI category, from the prevalence of 54.1%, 63.6%, 75.9% and 87.4% with corresponding odds ratios of 1.55, 2.77, and 6.31 for BMI ≥18.5-22.9 kg/m2, 23-24.9 kg/m2 and ≥25 kg/m2, respectively. The odds of being MUH tends to increase when BMI level increases. Other characteristics associated with MUH were being female, being older, having a low level of education, living in a rural area and currently smoking tobacco. In this national representative sample of the Thai general population, the prevalence of MUH was high and rose continuously with increasing BMI levels. MUH was also prevalent in normal weight and underweight individuals.